From care to agency : the associative commitment of immigrant women from sub-Saharan Africa in the fight against HIV/AIDS in France - (:unkn) unknown (My University, 2016)
The French associative landscape against HIV/AIDS sees at the end of the 1990s the emergence of a set of immigrant organizations, especially led by persons born in sub-Saharan Africa. Heavily affected by the epidemic and long forgotten by the programs to combat the epidemic, immigrant women became a priority target of the health authorities and now occupy a particular position within immigrant organizations. The objective of this thesis is to shed light on the specific role played by women born in sub-Saharan Africa in the fight against HIV/AIDS in France and to analyze the consequences of such an associative commitment on various spheres of their lives. A socio-ethnographic survey was conducted in the Ile-de-France region, between 2011 and 2013, from the observation of the daily lives, actions and events of six organizations. Eighty-six interviews were conducted among women met in twelve organizations, in order to reconstruct their biographical trajectory. Twenty-six doctors, nurses and hospital social workers were interviewed in order to seize their representations of these associative players. Theories of care and agency form the analytical framework emerging from the empirical materials. The survey shows that the associative projects led by women born in sub-Saharan Africa respond sensitively to the needs of the most vulnerable immigrants but also to the needs of the social and health professionals. Predominantly female, these groups fit into an associative grammar of care based on self-support and the meeting between two profiles: the female users in a liminal position and the caregivers with diverse resources. The female users draw on these spaces the necessary supports to get out of the liminal status, while the caregivers develop a field expertise which allows them to fit into HIV/AIDS policies and professional spheres. The analyses point out the agency process of the women engaged within these organizations. The female users negotiate the mode
Keywords: African Research